2019
DOI: 10.1097/md.0000000000016023
|View full text |Cite
|
Sign up to set email alerts
|

Urinary retention as a postoperative complication associated with functional decline in elderly female patients with femoral neck and trochanteric fractures

Abstract: Urinary retention (UR) has been recognized as one of the most common postoperative complications after hip surgery in elderly. The objective of the present study was to evaluate risk for postoperative complications of UR in elderly female patients with femoral neck fractures. We recruited 221 female patients (age 85.3 ± 7.0 years) with a history of hip surgery carried out at Toyama Municipal Hospital. UR occurred in 34 out of 221 cases (15.4%). Multiple logistic regression analysis was conducted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
0
15
0
2
Order By: Relevance
“…It adversely affects the functional outcome of female patients but is not associated with increased mortality rates [10]. Our retrospective study has demonstrated that cognitive function as well as ADL were the important risk factors for urinary retention, suggesting that the postoperative management of urinary retention is important with taking account of neurofunctional assistance and nursing care in daily living, especially in elderly female patients receiving surgery of femoral neck and trochanteric fractures [11]. Complications after hip fracture surgery were common.…”
Section: Discussionmentioning
confidence: 87%
“…It adversely affects the functional outcome of female patients but is not associated with increased mortality rates [10]. Our retrospective study has demonstrated that cognitive function as well as ADL were the important risk factors for urinary retention, suggesting that the postoperative management of urinary retention is important with taking account of neurofunctional assistance and nursing care in daily living, especially in elderly female patients receiving surgery of femoral neck and trochanteric fractures [11]. Complications after hip fracture surgery were common.…”
Section: Discussionmentioning
confidence: 87%
“…In a 2019 retrospective cohort study in which 221 female patients (age 85.3 ± 7.0 years) with a history of hip surgery, urinary retention occurred in 34 out of the 221 cases (15.4%) and was significantly associated with cognitive impairment (OR 4.11, 95% CI 1.53-11.03, P = 0.005) and ADL (OR 2.61, 95% CI 1.11-6.18, P = 0 .029), under adjustment with age and body mass index (BMI). This study demonstrated that cognitive function and ADL were important risk factors for urinary retention, and suggested that the postoperative management of urinary retention is important when considering neurofunctional assistance and nursing care in daily living, especially in elderly female patients undergoing surgery after femoral neck and trochanteric fractures [171]. A 2014 clinical study of risk factors for urinary retention including 72 fe-male elderly patients undergoing hip surgery showed that the early removal of the urethral catheter (per 1-day indwelling period increase, OR 0.33, 95% CI 0.11-0.96, P = 0.04) and preoperative dementia and/or delirium (OR 10.4, 95% CI 1.21-89.2, P = 0.03) had significant correlations with postoperative urinary retention.…”
Section: Prevention Of Urinary Tract Infectionsmentioning
confidence: 80%
“…AUR causes multiple acute (pain, discomfort, decreased consciousness) and late (urinary tract infections, sepsis, urinary incontinence) complications [12,24]. Between the main risk factors we can nd the rst 24 postoperative hours and being male, due to the increase in the size of the prostate, but AUR may be also adversely affected by cognitive impairment, hypothyroidism, vascular insu ciency, the administration of drugs such as opioids and the rest in bed because of the hip fracture [25]. The prevalence of AUR described in the literature is very variable (5-70%) [12,24] being in our sample 11.3% in 2012 and 46.3% in 2017.…”
Section: Discussionmentioning
confidence: 99%